Perancangan Ulang Visual Branding Noir Coffee & Space untuk Memperkuat Brand Identity Bisnis Model B2b - Kevin Christian Arisandy; Khamadi (LP2M Sekolah Tinggi Seni Rupa dan Desain Visi Indonesia (STSRD VISI), 2021)
Noir is a coffeeshop established since 2019 that didn't have well-known visual branding. By the time, Noir made some innovations and started to focus on developing B2B model business. The objective of this rebranding project was to create a new positive image which could deliver the message of Noir's to the audience. The methods used in this rebranding project were analysing the logo with the theory of David E Carter, SWOT matrix analysis, variable constant, and brainstorming. Therefore, the logo created could deliver the message of Noir's as B2B model business which was opened for doing professional partnership. Moreover, this project also designed the supported media that had a function to strengthen the visual image to introduce the product to the public.